Evaluasi Efektivitas Behaviorally Anchored Rating Scales (BARS) untuk Penilaian Kinerja Karyawan di Toko Bahan Bangunan Sampurna - Kusumawati, Aulia; Winarno, Heru; Bob Anthony, Muhamad; Putra Wahyudi, Refli (Fakultas Teknik Universitas Tulang Bawang, 2026)
The problem of Sampurna Building Store has not conducted employee performance assessments based on employee behavior when running it, resulting in the performance results of each employee being reviewed directly and the actions that must be taken to improve the performance of undisciplined employees. This study is to find out how to design employee performance assessments and solutions to improve employee productivity, then the researcher conducted an analysis using the Behaviorally Anchor Rating Scale and SPSS methods. Questionnaires were given to 15-25 employees and 30-50 loyal customers who bought Building material products. From the results of the analysis, the dimensions that need to be improved are Reliability and Work Behavior. By improving Reliability and Work Behavior, it is expected to overcome the design of performance assessments so that employees can work harder, comfortably and motivated. Based on data analysis, it is known that employee performance based on behavior (Behaviorally Anchored Rating Scales) at Sampurna Building Store is in the high assessment category with an average of 67.02%, while data analysis shows that work performance from a customer perspective based on behavior at Sampurna Building Store is in the high assessment category with an average of 72.99%. Keywords: Human resources, Performance Appraisal, Reliability, Work Behavior